IMPLEMENTATION OF POLICE REGULATION NUMBER 7 OF 2022 CONCERNING THE PROFESSIONAL CODE OF ETHICS AND THE POLICE CODE OF ETHICS COMMISSION AGAINST VIOLATIONS BY POLICE MEMBERS - Hayqal, Dani (International Journal of Innovative Technologies in Social Science, 2022)
A professional code of ethics is a standard created and accepted by a group of professions to advise or instruct members of the profession on how to control the profession and preserve its excellence. Professional ethics is applicable to all extant professions, including the legal profession. The National Police of the Republic of Indonesia (POLRI) is one of the law enforcement professions that has a code of professional ethics. This research intends to identify and analyse the code of ethics and punishment of Polri members who conduct illegal activities in accordance with National Police Regulation Number 7 of 2022 regarding the Professional Code of Ethics and the Police Code of Ethics Commission. This investigation is descriptive and analytical. This study’s methodology employs normative legislation and an empirical strategy and the data are then analysed qualitatively. The findings revealed that the implementation of National Police Regulation (Perpol) 7 of 2022 regarding Code of Professional Ethics of the Indonesian National Police (KEPP) and Indonesian National Police Code of Conduct Commission (KKEP) is a new Police Regulation that replaces the Regulation of the National Police Chief of the Republic of Indonesia Number 14 of 2011 regarding the Police Professional Code of Ethics and the Regulation of the Head of the State Police of the Republic of Indonesia Number 19 of 2012 regarding the Organization and Work Procedures of the Code Commission Ethics of the Indonesian National Police.